Nocturnal pollination: an overlooked ecosystem service vulnerable to environmental change. Issue 1 (1st June 2020) - Macgregor, Callum J.; Scott-Brown, Alison S.
Abstract : Existing assessments of the ecosystem service of pollination have been largely restricted to diurnal insects, with a particular focus on generalist foragers such as wild and honey bees. As knowledge of how these plant-pollinator systems function, their relevance to food security and biodiversity, and the fragility of these mutually beneficial interactions increases, attention is diverting to other, less well-studied pollinator groups. One such group are those that forage at night. In this review, we document evidence that nocturnal species are providers of pollination services (including pollination of economically valuable and culturally important crops, as well as wild plants of conservation concern), but highlight how little is known about the scale of such services. We discuss the primary mechanisms involved in night-time communication between plants and insect pollen-vectors, including floral scent, visual cues (and associated specialized visual systems), and thermogenic sensitivity (associated with thermogenic flowers). We highlight that these mechanisms are vulnerable to direct and indirect disruption by a range of anthropogenic drivers of environmental change, including air and soil pollution, artificial light at night, and climate change. Lastly, we highlight a number of directions for future research that will be important if nocturnal pollination services are to be fully understood and ultimately conserved.